EMOTIONAL INTELLIGENCE, SPIRITUAL, INTELLECTUAL AND CONDUCT STUDY ON THE LEVEL OF UNDERSTANDING OF ACCOUNTING (Empirical Study of Accounting Students in Colleges in Lampung) - Husein Pulungan, Muhammad Sadat; Siregar, Nolita Yeni (Prosiding International conference on Information Technology and Business (ICITB), 2016)
Accounting Education held at the college on the production so that students can work as a Professional Accountant. To be able to produce quality graduates that universities should continue to improve the quality of the education system. Nuraini, 2007. worrying lack of clarity on the accounting industry generated by higher education accounting, this is because many colleges are not able to make good their students master the knowledge and life skills. This study aimed to get empirical evidence of emotional intelligence, spiritual intelligence, intellectual intelligence, learning behavior to the level of understanding of accounting, which could eventually help the college improve students ability to understand accounting. The method used in this study is a survey method in which the model of collecting data relevant to the research problem. The population in this study were students S1 minimal own half 5. The sample of at least half of a 5 because the student has experienced a long learning process and have benefited most from the teaching of accounting. The number of samples in this study were 200 students in accounting from College of Lampung. that ultimately this study is expected to assist private universities in Lampung to boost understanding of accounting by mapping the level of intelligence and understanding of accounting in each private university in Lampung.KEY WORDSUnderstanding accounting, intelligence, learning behavior